Water Sources and Personal Hygiene with Dermatitis - Michico Eloista Br. Ginting; Taufik Ashar; Eka Lestari Mahyuni (Universitas Aisyah Pringsewu, 2023)
Skin diseases are closely related to personal hygiene such as dermatitis. Water sources are one of the causes of dermatitis. This study aims to analyze the relationship between water sources and personal hygiene with the incidence of dermatitis. This research is a survey with a case-control design approach. This study involved 50 respondents in each case and control group. Data were collected using a questionnaire and analyzed using chi-square and multiple logistic regression. The results found that there was a significant relationship between water sources, bathing behavior, hand washing behavior, and changing habits with the incidence of dermatitis p-value less than 0.001; less than 0.001; 0.001; less than 0.001, while there is no relationship between nail-cutting habits and dermatitis with a p-value of 0.091. Changing clothing habits variable is the most influential variable in this study with an Exp. B=68,714. It is recommended that to improve health education and cooperation with the Munten sub-district government, Karo Regency assisted by village Kader or one of them environmental health workers to overcome and prevent environmental-based diseases. Abstrak: Penyakit kulit erat hubungannya dengan kebersihan pribadi seperti dermatitis. sumber air salah satu penyebab kejadian dermatitis. Penelitian ini bertujuan untuk untuk menganalisis hubungan sumber air dan personal hygiene dengan kejadian dermatitis. Penelitian ini adalah surevei dengan pendekatan rancangan kasus kontrol. Penelitian ini melibatkan 50 respondent tiap kelompok kasus dan kontrol. Data dikumpulkan dengan menggunakan kuesioner dan dianalisis menggunakan chi-square dan multiple logistic regression. Hasil ditemukan bahwa ada hubungan yang signifikan antara sumber air, perilaku mandi, perilaku cuci tangan, dan kebiasaan ganti baju dengan kejadian dermatitis p-value kurang dari 0,001; kurang dari 0,001; 0,001; kurang dari 0,001, sedangkan tidak ada hubungan antara kebiasaan memotong kuku dengan dermatitis dengan p-value 0,091. Changing clothing habits variable is the most influential variable in this study with an Exp. B=68,714. Disarankan bahwa untuk meningkatkan pendidikan kesehatan dan kerjasama dengan pemerintah kecamatan Munten Kabupaten Karo dibantu oleh kader desa atau salah satunya petugas kesehatan penyehatan lingkungan untuk mengatasi dan mencegah penyakit berbasis lingkungan